Emotions in the face: biology or culture? – Using idiomatic constructions as indirect evidence to inform a psychological research controversy - Langlotz, Andreas (Linguistik Online, 2018)
Research on the facial expression of emotions has become a bone of contention in psychological research. On the one hand, Ekman and his colleagues have argued for a universal set of six basic emotions that are recognized with a considerable degree of accuracy across cultures and automatically displayed in highly similar ways by people. On the other hand, more recent research in cognitive science has provided results that are supportive of a cultural-relativist position. In this paper this controversy is approached from a contrastive perspective on phraseological constructions. It focuses on how emotional displays are codified in somatic idioms in some European (English, German, French, Spanish) and East Asian (Japanese, Korean, Chinese [Cantonese]) languages. Using somatic idioms such as make big eyes or die Nase rümpfen as a pool of evidence to shed linguistic light on the psychological controversy, the paper engages with the following general research question: Is there a significant difference between European and East Asian somatic idioms or do these constructions rather speak for a universal apprehension of facial emotion displays? To answer this question, the paper compares somatic expressions that are selected from (idiom) dictionaries of the languages listed above. Moreover, native speakers of the East Asian languages were consulted to support the analysis of the respective data. All corresponding entries were analysed categorically, i. e. with regard to whether or not they encode a given facial area to denote a specific emotion. The results show arguments both for and against the universalist and the cultural-relativist positions. In general, they speak for an opportunistic encoding of facial emotion displays.